High-strength and high-toughness nanofiber composite membrane and preparation method thereof
Through the "two-step cross-linking method" and thermal pressure treatment process, the high-strength and tough PVA-CO-PE nano-fiber composite film is prepared, which solves the problem of insufficient strength and toughness of nanofiber membrane in the existing technology, and achieves higher Mechanical properties and simpler preparation processes.
Patent Information
- Application Number
- CN202411287464.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The phase-change nanofiber membranes prepared in the prior art only pass through one cross-linking reaction, and their strength and toughness are poor, limiting their application range.
Using the "two-step cross-linking method" and hot-pressing treatment process, after the first cross-linking, deionized water is added for the second cross-linking, and then hot-pressing treatment is performed to prepare high-strength and high-toughness PVA-co-PE nanometers. Fiber composite membrane.
It improves the tensile strength and stretching of nano fiber compound membrane, which enhances its physical and mechanical properties, solves the problem of insufficient mechanical properties, and provides a new way for preparing high -performance materials.
Smart Images

Figure CN119350672A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of preparation of nanofiber membrane materials, and in particular to a high-strength and high-toughness nanofiber composite membrane and a preparation method thereof. Background Art
[0002] With the continuous advancement of science and technology and the development of new materials science, the demand for high-performance materials is increasing, especially in the fields of smart wearables, flexible electronic devices, biomedicine and environmental protection. However, the insufficient mechanical properties of materials often limit their application areas. Among many new materials, nanofiber materials have attracted widespread attention due to their unique physical and chemical properties, ultra-high specific surface area and excellent mechanical properties. As an important polymer composite material, polyvinyl alcohol-co-polyethylene (PVA-co-PE) nanofibers have shown great application potential in biomedical engineering, filtration materials, environmental protection and flexible electronic devices due to their unique physical and chemical properties, good biocompatibility, and environmental protection and sustainable development.
[0003] In the prior art, a method for preparing phase-change nanofibers is disclosed in the patent with publication number CN 107620212 A. The patent grafts the phase-change medium onto a carrier by condensation polymerization to form a phase-change nanofiber with a cross-linked network structure, wherein the carrier is prepared by dissolving PVA-co-PE nanofibers into a suspension, then mixing with the phase-change material, adding a cross-linking agent for cross-linking, washing by centrifugation with a solvent, and then drying to obtain the phase-change nanofibers. The fiber membrane is obtained by only one cross-linking reaction, and its strength and toughness are poor, which limits its application scope to a certain extent.
[0004] In view of this, it is necessary to design an improved nanofiber composite membrane and a preparation method thereof to solve the above problems. Summary of the invention
[0005] The purpose of the present invention is to provide a high-strength and high-toughness nanofiber composite membrane and a preparation method thereof. A PVA-co-PE nanofiber composite membrane is prepared by a "two-step crosslinking method" and a hot pressing process. The nanofiber composite membrane has the characteristics of high strength and good toughness, and the preparation process is simple. No additional chemical reagents need to be added for further crosslinking. This not only solves the problem of insufficient mechanical properties of nanofiber materials, but also provides a new way to prepare high-performance materials.
[0006] To achieve the above-mentioned object of the invention, the present invention provides a high-strength and high-toughness nanofiber composite membrane and a preparation method thereof, comprising the following steps:
[0007] S1. dispersing PVA-co-PE nanofibers in a solvent to obtain a first nanofiber suspension;
[0008] S2. adding a crosslinking agent to the first nanofiber suspension to perform a first crosslinking, and obtaining a second nanofiber suspension after sufficient reaction;
[0009] S3. adding a predetermined amount of deionized water to the second nanofiber suspension to perform a second crosslinking to obtain a third nanofiber suspension after sufficient reaction;
[0010] S4. performing solid-liquid separation on the third nanofiber suspension to obtain a PVA-co-PE nanofiber composite membrane;
[0011] S5. Performing hot pressing treatment on the nanofiber composite membrane to obtain a high-strength and high-toughness nanofiber composite membrane.
[0012] As a further improvement of the present invention, in step S3, the amount of deionized water added is 5-15 wt % of the mass of the second nanofiber suspension.
[0013] As a further improvement of the present invention, in step S5, during the hot pressing process, the hot pressing temperature is 85-95°C, the pressure is 8-12 MPa, and the hot pressing time is 55-65s.
[0014] As a further improvement of the present invention, in step S1, the mass fraction of the PVA-co-PE nanofibers in the first nanofiber suspension is 1 to 2 wt%.
[0015] As a further improvement of the present invention, in step S1, the solvent includes isopropanol and deionized water; the mass ratio of isopropanol to deionized water is 60-70:40-30.
[0016] As a further improvement of the present invention, in step S2, the cross-linking agent is glutaraldehyde.
[0017] As a further improvement of the present invention, in step S2, the amount of the cross-linking agent added accounts for 1wt% to 4wt% of the mass of the PVA-co-PE nanofibers.
[0018] As a further improvement of the present invention, in step S4, the solid-liquid separation method is: vacuum assisted filtration method is used for suction filtration treatment.
[0019] The present invention also provides a high-strength and high-toughness nanofiber composite membrane, which is prepared by the above-mentioned method for preparing the nanofiber composite membrane, through a first cross-linking reaction with a cross-linking agent, and then hydrogen bonding with deionized water, a second cross-linking reaction occurs, and then combined with a hot pressing process to obtain a high-strength and high-toughness nanofiber composite membrane.
[0020] As a further improvement of the present invention, the tensile strength of the high-strength and high-tenacity nanofiber composite membrane is 17.8MPa to 35.6MPa, and the tensile fracture strain is 9.3% to 34.9%.
[0021] The beneficial effects of the present invention are:
[0022] 1. The method for preparing a high-strength and high-toughness nanofiber composite membrane provided by the present invention comprises the following steps: first preparing a stable PVA-co-PE nanofiber suspension, then adding a cross-linking agent to produce a first cross-linking reaction, and after sufficient reaction, adding deionized water to break the equilibrium state of the mixed solution, so that the polar groups (hydroxyl groups) in the PVA-co-PE nanofibers interact with water molecules, thereby generating a large number of hydrogen bonds between the PVA-co-PE nanofibers and generating a second self-cross-linking reaction. This step greatly increases the physical and mechanical properties of the PVA-co-PE nanofiber composite membrane, and this method does not require the addition of other chemical reagents, the preparation method is simple, and is convenient for industrial applications.
[0023] 2. The method for preparing a high-strength and high-toughness nanofiber composite membrane provided by the present invention can quickly evaporate the water molecules inside the PVA-co-PE nanofiber composite membrane by hot pressing the PVA-co-PE nanofiber composite membrane after secondary cross-linking, thereby reducing the porosity without damaging the PVA-co-PE nanofibers, and at a specific temperature, the PVA-co-PE nanofibers present a similar molten state, and then apply pressure to allow the PVA-co-PE nanofibers to be better cross-linked, thereby further improving the strength of the PVA-co-PE nanofiber composite membrane.
[0024] 3. The present invention combines the "two-step cross-linking method" with the hot pressing process to prepare a nanofiber composite membrane with high strength and toughness, which makes up for the problem of insufficient mechanical properties of most current polymer composite materials. In addition, its preparation process is simple, providing a new way to prepare high-performance materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A schematic flow chart of the method for preparing the high-strength and high-toughness nanofiber composite membrane provided by the present invention.
[0026] Figure 2 These are high-magnification and low-magnification SEM images of the nanofiber composite membranes prepared in Examples 1 to 4 and Comparative Examples 1 to 2.
[0027] Figure 3 1 and 2 are stress-strain diagrams of the nanofiber composite membranes prepared in Examples 1 to 4 and Comparative Examples 1 to 2.
[0028] Figure 41 and 2 are stress-strain diagrams of the nanofiber composite membranes prepared in Example 1 and Comparative Examples 3 to 4. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0030] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.
[0031] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0032] See also Figure 1 As shown, the present invention provides a method for preparing a high-strength and high-toughness nanofiber composite membrane, comprising the following steps:
[0033] S1. Dispersing and mixing the solvent and PVA-co-PE nanofibers in a high-speed shearing machine to obtain a first nanofiber suspension;
[0034] S2. adding a crosslinking agent to the first nanofiber suspension obtained in step S1 to perform a first crosslinking, and obtaining a second nanofiber suspension after sufficient reaction;
[0035] S3. adding a predetermined amount of deionized water to the second nanofiber suspension to perform a second crosslinking to obtain a third nanofiber suspension after sufficient reaction;
[0036] S4. performing solid-liquid separation on the third nanofiber suspension to obtain a PVA-co-PE nanofiber composite membrane;
[0037] S5. Performing hot pressing treatment on the nanofiber composite membrane to obtain a high-strength and high-toughness nanofiber composite membrane.
[0038] Through the above-mentioned method, the present invention can obtain a high-strength and high-toughness nanofiber composite membrane, the preparation process is simple, and the physical and mechanical properties of the prepared nanofiber composite membrane are greatly improved.
[0039] Preferably, in step S1, the solvent includes isopropanol and deionized water, the mass ratio of isopropanol to deionized water is 60-70:40-30, and the mass fraction of PVA-co-PE nanofibers is 1-2wt% to obtain a stable PVA-co-PE nanofiber suspension.
[0040] In step S2, the cross-linking agent is preferably glutaraldehyde, and the amount of the cross-linking agent added accounts for 1 wt% to 4 wt% of the mass of the PVA-co-PE nanofibers.
[0041] In step S3, the addition of deionized water breaks the phase equilibrium of the second nanofiber suspension, so that a large number of hydrogen bonds are formed between the PVA-co-PE nanofibers. The mass fraction of the deionized water is preferably 5-15 wt%.
[0042] If too little deionized water is added, the PVA-co-PE nanofibers cannot fully react with water molecules, and a large number of hydrogen bonds cannot be formed between the PVA-co-PE nanofibers, resulting in poor cross-linking effect, so that the mechanical properties of the PVA-co-PE nanofiber composite membrane cannot be well improved. If too much deionized water is added, the dispersion effect of the PVA-co-PE nanofibers will be worse, and a solution state cannot be formed, but a solid-liquid separation state will be presented.
[0043] In step S4, the solid-liquid separation method is preferably: vacuum assisted filtration is used for suction filtration, and specifically, a vacuum filter can be used for suction filtration.
[0044] In step S5, during the hot pressing process, the hot pressing temperature is preferably 85-95°C, the hot pressing pressure is preferably 8-12 MPa, and the hot pressing time is preferably 55-65s; if the hot pressing temperature and pressure are too high, the PVA-co-PE nanofiber membrane will be unable to be formed and its strength will deteriorate. If the temperature and pressure are too low, the mechanical properties of the PVA-co-PE nanofiber membrane will hardly change, and the purpose of assisting in promoting cross-linking and enhancing the mechanical properties of the PVA-co-PE nanofiber membrane will not be achieved.
[0045] The present invention also provides a high-strength and high-toughness nanofiber composite membrane, which is prepared by the above-mentioned method for preparing the nanofiber composite membrane, and the high-strength and high-toughness nanofiber composite membrane is obtained by a "two-step crosslinking method" combined with a hot pressing process.
[0046] The present invention is described in detail below with reference to specific embodiments.
[0047] Example 1
[0048] This embodiment provides a method for preparing a high-strength and high-toughness nanofiber composite membrane, comprising the following steps:
[0049] S1. Mix isopropyl alcohol and deionized water in a ratio of 60:40 to prepare a solvent; disperse and mix the PVA-co-PE nanofibers and the prepared solvent in a high-speed shearing machine to obtain a first nanofiber suspension. In the first nanofiber suspension, the mass fraction of the PVA-co-PE nanofibers is 1wt%.
[0050] S2. Add glutaraldehyde to the first nanofiber suspension obtained in step S1, perform the first crosslinking, and stir for 2 hours to allow it to fully react to obtain a second nanofiber suspension; wherein the amount of the crosslinking agent added accounts for 1wt% of the mass of the PVA-co-PE nanofibers.
[0051] S3. Weigh a predetermined amount of deionized water so that the deionized water accounts for 5wt% of the mass of the second nanofiber suspension, add the deionized water to the second nanofiber suspension obtained in step S2, perform a second crosslinking, and stir for 2h to fully react to obtain a third nanofiber suspension;
[0052] S4. The third nanofiber suspension obtained in step S3 is filtered by a vacuum filter to obtain a PVA-co-PE nanofiber composite membrane;
[0053] S5. The PVA-co-PE nanofiber composite membrane obtained in step S4 is hot-pressed at 90° C. and a pressure of 10 MPa for 60 seconds using a hot press to obtain a high-strength and high-toughness nanofiber composite membrane.
[0054] Examples 2 to 4 and Comparative Examples 1 to 2
[0055] Examples 2 to 4 and Comparative Examples 1 to 2 respectively provide a method for preparing a high-strength and high-toughness nanofiber composite membrane. Compared with Example 1, the difference is that the amount of deionized water added in step S3 is changed. The amount of deionized water added in each example and Comparative Examples 1 to 2 is shown in Table 1, and the other steps are substantially the same as in Example 1, which will not be repeated here.
[0056] Table 1 Amount of deionized water added in Examples 1 to 4 and Comparative Examples 1 to 2
[0057]
[0058] The appearance of the high-strength and high-toughness nanofiber composite membranes prepared in Examples 1 to 4 and Comparative Examples 1 to 2 are as follows: Figure 2 The stress-strain curve is shown in Figure 3 shown.
[0059] Figure 2 and Figure 3In the figure, PVA-co-PE, PVA-co-PE-S, PVA-co-PE-S1, PVA-co-PE-S2, PVA-co-PE-S3, and PVA-co-PE-S4 represent the high-strength and high-toughness nanofiber composite membranes prepared in Comparative Example 1, Example 1, Example 2, Example 3, Example 4, and Comparative Example 2, respectively.
[0060] Figure 3 The specific values of tensile strength and tensile fracture strain of the high-strength and high-toughness nanofiber composite membranes prepared in Examples 1 to 4 and Comparative Examples 1 to 2 are shown in Table 2.
[0061] Table 2 Tensile strength and tensile fracture strain of the composite films in Examples 1 to 4 and Comparative Examples 1 to 2
[0062]
[0063] Combination Figure 2 and Figure 3 It can be seen that with the increase in the amount of deionized water added, the tensile strength and tensile fracture strain of the obtained high-strength and high-toughness nanofiber composite membrane gradually increase, indicating that the strength and flexibility of the nanofiber composite membrane gradually increase, but when the amount of deionized water added reaches 15wt%, if it is further increased to 25wt%, the dispersion effect of the PVA-co-PE nanofibers will deteriorate, and a solution state cannot be formed, but a solid-liquid separation state is presented, which makes it difficult to form the nanofiber composite membrane, and the tensile strength and flexibility are reduced.
[0064] Comparative Examples 3-4
[0065] Comparative Examples 3 and 4 respectively provide a method for preparing a high-strength and high-toughness nanofiber composite membrane. Compared with Example 1, the difference is that the hot pressing treatment method in step S5 is changed: in Comparative Example 3, the hot pressing treatment is changed to a drying treatment at 50°C; in Comparative Example 4, the hot pressing temperature of the hot pressing treatment is changed to 120°C and the pressure is changed to 20MPa. The other steps are substantially the same as those in Example 1 and will not be repeated here.
[0066] The stress-strain curves of the high-strength and high-toughness nanofiber composite membranes prepared in Comparative Examples 3 to 4 are as follows: Figure 4 The specific values of its tensile strength and tensile fracture strain are shown in Table 3.
[0067] Table 3 Tensile strength and tensile fracture strain of the composite films in Comparative Examples 3 to 4
[0068] Comparative Example Comparative Example 3 Comparative Example 4 tensile strength 17.0MPa 5.2MPa Tensile fracture strain 8.6% 4.6%
[0069] Figure 4In the table, PVA-co-PE-S5 and PVA-co-PE-S6 represent the high-strength and high-toughness nanofiber composite membranes prepared in Comparative Examples 3 and 4, respectively. Figure 4 It can be seen that compared with Example 1, in Comparative Example 3, the temperature is too low, so the nanofibers cannot present a similar molten state, and the nanofibers cannot be further cross-linked. Therefore, the tensile strength and flexibility of Comparative Example 3 are reduced. Compared with Example 1, due to the high temperature and pressure, the nanofibers are very close to the molten state, resulting in the nanofiber composite film being difficult to form and extremely easy to break under high pressure conditions. Therefore, the tensile strength and flexibility of Comparative Example 4 are sharply reduced.
[0070] In summary, the present invention combines the "two-step cross-linking method" with the hot pressing process to prepare a nanofiber composite membrane with high strength and toughness, which makes up for the problem of insufficient mechanical properties of most current polymer composite materials. In addition, its preparation process is simple. Only by adding a specific proportion of deionized water can the PVA-co-PE nanofibers further produce a self-cross-linking reaction, which provides a new way to prepare high-performance materials.
[0071] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a high-strength and high-toughness nanofiber composite membrane, characterized in that: The steps include: S1. dispersing PVA-co-PE nanofibers in a solvent to obtain a first nanofiber suspension; S2. adding a crosslinking agent to the first nanofiber suspension to perform a first crosslinking, and obtaining a second nanofiber suspension after sufficient reaction; S3. adding a predetermined amount of deionized water to the second nanofiber suspension to perform a second crosslinking to obtain a third nanofiber suspension after sufficient reaction; S4. performing solid-liquid separation on the third nanofiber suspension to obtain a PVA-co-PE nanofiber composite membrane; S5. Performing hot pressing treatment on the nanofiber composite membrane to obtain a high-strength and high-toughness nanofiber composite membrane.
2. The method for preparing a high-strength and high-toughness nanofiber composite membrane according to claim 1, characterized in that: In step S3, the amount of deionized water added is 5-15 wt % of the mass of the second nanofiber suspension.
3. The method for preparing a high-strength and high-toughness nanofiber composite membrane according to claim 1, characterized in that: In step S5, during the hot pressing process, the hot pressing temperature is 85-95°C, the pressure is 8-12 MPa, and the hot pressing time is 55-65 seconds.
4. The method for preparing a high-strength and high-toughness nanofiber composite membrane according to claim 1, characterized in that: In step S1, the mass fraction of PVA-co-PE nanofibers in the first nanofiber suspension is 1-2 wt%.
5. The method for preparing a high-strength and high-toughness nanofiber composite membrane according to claim 1, characterized in that: In step S1, the solvent includes isopropanol and deionized water; the mass ratio of isopropanol to deionized water is 60-70:40-30.
6. The method for preparing a high-strength and high-toughness nanofiber composite membrane according to claim 1, characterized in that: In step S2, the cross-linking agent is glutaraldehyde.
7. The method for preparing a high-strength and high-toughness nanofiber composite membrane according to claim 1, characterized in that: In step S2, the amount of the cross-linking agent added is 1 wt% to 4 wt% of the mass of the PVA-co-PE nanofibers.
8. The method for preparing a high-strength and high-toughness nanofiber composite membrane according to claim 1, characterized in that: In step S4, the solid-liquid separation method is: vacuum assisted filtration method is used for suction filtration.
9. A high-strength and high-toughness nanofiber composite membrane, characterized in that: The high-strength and high-toughness nanofiber composite membrane is prepared by the preparation method of any one of claims 1 to 8.
10. The high-strength and high-toughness nanofiber composite membrane according to claim 9, characterized in that: The high-strength and high-tenacity nanofiber composite membrane has a tensile strength of 17.8 MPa to 35.6 MPa, and a tensile fracture strain of 9.3% to 34.9%.
Citation Information
Patent Citations
Preparation method of phase change nano fiber
CN107620212A
Anti-pollution degerming nanofiber filter membrane and preparation method thereof
CN112246112A
Immunochromatography test strip based on nano-fiber membrane with gradient pore size distribution and preparation method of immunochromatography test strip
CN114544945A
Preparation method of water-stable antibacterial traditional Chinese medicine composite nanofiber membrane based on PVA (Polyvinyl Alcohol)
CN116289203A
Double-layer composite nanofiber membrane with photothermal conversion function and preparation method thereof
CN118273002A